(untitled) (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2015)
The authors László Varga, PhD and Réka Zsámboki Kissné, PhD are both specialized and proven researchers in education with an emphasis on early childhood education. László Varga in addition to acting as the Leader of the Research Team also serves as the Creative Editor of the study results as well as the Research Coordinator of the international project.